2019
DOI: 10.3390/ijms20215302
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Effects of Grifola frondosa Heteropolysaccharide on NAFLD and Regulation of the Gut Microbiota

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a major public health problem in many countries. In this study, the ability of Grifola frondosa heteropolysaccharide (GFP) to ameliorate NAFLD was investigated in rats fed a high-fat diet (HFD). The molecular mechanisms modulating the expression of specific gene members related to lipid synthesis and conversion, cholesterol metabolism, and inflammation pathways were determined. The components of the intestinal microflora in rats were analyzed by high-throughput next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…RSV could increase the proportion of Allobaculum . Previous studies have proven that increases in Allobaculum are beneficial to HFD mice ( Raza et al, 2017 ; Li et al, 2019 ). Allobaculum shows increases when dietary fiber is taken and is negatively related to the concentration of leptin ( Ravussin et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…RSV could increase the proportion of Allobaculum . Previous studies have proven that increases in Allobaculum are beneficial to HFD mice ( Raza et al, 2017 ; Li et al, 2019 ). Allobaculum shows increases when dietary fiber is taken and is negatively related to the concentration of leptin ( Ravussin et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, GFP has also been found to regulate the gut microbiota of rats with non-alcoholic fatty liver disease (NAFLD). Li and coworkers found that GFP could partly recover the HFD-induced alteration of cecal microbiota structure [ 30 ]. GFP treatment could decrease the Firmicutes to Bacteroidetes ratio, indicating a lower possibility of lipid production from undigested carbohydrates [ 108 ].…”
Section: Biological Activities and Medicinal Propertiesmentioning
confidence: 99%
“…Friedman also suggested in his review that the ratio decrease of the two major classes of gut bacteria, namely, Firmicutes and Bacteroides , could have fat-lowering effects in obesity treatment [ 106 ]. In addition, GFP supplementation significantly increased the proportion of Allobaculum , Bacteroides , Bifidobacterium and some other microbial groups in the cecal microbiota, which might boost the immune system of the host and the defense against NAFLD [ 30 ]. The boosting of the immune system may contribute to the anti-tumor and anti-inflammatory effect of GFP as well [ 29 , 111 ].…”
Section: Biological Activities and Medicinal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding GF, it has been shown that a polysaccharide given orally had a similar protective effect on non-alcoholic steato-hepatitis in rats as AbM had in mice above [66]. The mechanism was a beneficial regulation of gut microbiota [79]. Moreover, a fermented GF extract had anti-inflammatory effect in an endotoxin-induced uveitis model in rats [80], and a GF extract reduced colon ulceration in an IBD rat model through an antioxidative and anti-inflammatory mechanism [81].…”
Section: Gfmentioning
confidence: 98%